2019
DOI: 10.1016/j.neuron.2019.07.013
|View full text |Cite
|
Sign up to set email alerts
|

SETD5 Regulates Chromatin Methylation State and Preserves Global Transcriptional Fidelity during Brain Development and Neuronal Wiring

Abstract: Highlights d Loss of SETD5 impairs brain development and neuronal functions d Setd5 mutant mice exhibit cognitive and sociobehavioral deficits d SETD5 loss leads to an unfavorable chromatin state for RNA elongation and splicing d SETD5 has intrinsic histone methyltransferase activity for H3K36

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(122 citation statements)
references
References 92 publications
14
103
4
Order By: Relevance
“…In addition, specific hPTMS are strongly associated with different splicing types. H3K36me3 marks splicing related exons as shown in studies profiling H3K36me3 enrichment as lower in alternative splicing exons than constitutive exons (Hu et al, 2017;Kolasinska-Zwierz et al, 2009;Luco et al, 2010;Sessa et al, 2019;Wilhelm et al, 2011). H3K36me3 also facilitates efficient mRNA splicing through recruitment of an "adapter protein" to stabilize splice factors and regulate proper co-transcriptional splicesome assembly (Leung et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, specific hPTMS are strongly associated with different splicing types. H3K36me3 marks splicing related exons as shown in studies profiling H3K36me3 enrichment as lower in alternative splicing exons than constitutive exons (Hu et al, 2017;Kolasinska-Zwierz et al, 2009;Luco et al, 2010;Sessa et al, 2019;Wilhelm et al, 2011). H3K36me3 also facilitates efficient mRNA splicing through recruitment of an "adapter protein" to stabilize splice factors and regulate proper co-transcriptional splicesome assembly (Leung et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…We next sought to build on previous evidence that links Set2-dependent H3K36me3 to alternative splicing (De Almeida et al, 2011;Luco et al, 2010;Pajoro et al, 2017;Sessa et al, 2019;Xu et al, 2017;Yuan et al, 2017;Zhou et al, 2012). Although in higher eukaryotes multiple H3K36 methyltransferases catalyze H3K36me1 and H3K36me2, the yeast Set2 homolog is specific to H3K36me3 (McDaniel and Strahl, 2017;Sorenson et al, 2016;Strahl et al, 2002).…”
Section: Set2 Overexpression In Nac Regulated Alternative Splicing VImentioning
confidence: 99%
“…Methylation of histone complexes is another topic of interest, as many ASD genes are linked to chromatin remodeling. For example, SETD5 happloinsufficiency revealed that SETD5 methylates histones directly, suggesting an important role of H3K63 methylation, which in turn regulates RNA elongation and processing [56]. Together, these studies emphasize how important PTMs are for protein regulation and function.…”
Section: Identifying and Quantifying Post-translation Modificationsmentioning
confidence: 97%
“…Chromatin remodelers AT-rich interaction domain 1B (Arid1b) and chromodomain helicase DNA-binding protein 8 (Chd8) [216][217][218][219][220][221], histone methyltransferase euchromatic histone lysine methyltransferase 1 (Ehmt1) [222,223], and transcriptional regulators Foxp1 and Foxp2 [224][225][226][227][228][229][230][231] were targeted to investigate ASD-like behavioral phenotypes in mutated mice. SET domain-containing 5 (Setd5) was suggested as one of the histone methyltransferase candidates [232], but methyltransferase activity of Setd5 was not accepted by the majority of other researchers [233,234].…”
Section: Dna Methylationmentioning
confidence: 99%